An Occupational Therapy intervention for residents with stroke-related disabilities in UK Care Homes (OTCH): cluster randomised controlled trial with economic evaluation - Sackley, Catherine Mary; Walker, Marion F.; Burton, Christopher R.; Watkins, Caroline L.; Mant, Jonathan; Roalfe, Andrea K.; Wheatley, Keith; Sheehan, Bart; Sharp, Leslie; Stant, Katie E.; Fletcher-Smith, Joanna C.; Steel, Kerry; et al. (NIHR Health Technology Assessment Programme, 2016)
Background: Care home residents with stroke-related disabilities have significant activity limitations. Phase II trial results suggested a potential benefit of occupational therapy (OT) in maintaining residents’ capacity to engage in functional activity. Objective: To evaluate the clinical effectiveness and cost-effectiveness of a targeted course of OT in maintaining functional activity and reducing further health risks from inactivity for UK care home residents living with stroke-related disabilities. Design: Pragmatic, parallel-group, cluster randomised controlled trial with economic evaluation. Cluster randomisation occurred at the care-home level. Homes were stratified according to trial administrative centre and type of care provided (nursing or residential), and they were randomised 1 : 1 to either the intervention or the control arm. Setting: The setting was 228 care homes which were local to 11 trial administrative centres across England and Wales. Participants: Care home residents with a history of stroke or transient ischaemic attack, including residents with communication and cognitive impairments, not receiving end-of-life care. Intervention: Personalised 3-month course of OT delivered by qualified therapists. Care workers participated in training workshops to support personal activities of daily living. The control condition consisted of usual care for residents. Main outcome measures: Outcome data were collected by a blinded assessor. The primary outcome at the participant level was the Barthel Index of Activities of Daily Living (BI) score at 3 months. The secondary outcomes included BI scores at 6 and 12 months post randomisation, and the Rivermead Mobility Index, Geriatric Depression Scale-15 and European Quality of Life-5 Dimensions, three levels, questionnaire scores at all time points. Economic evaluation examined the incremental cost per quality-adjusted life-year (QALY) gain. Costs were estimated from the perspective of the NHS and Personal Social Services. Results: Overall, 568 residents from 114 care homes were allocated to the intervention arm and 474 residents from another 114 care homes were allocated to the control arm, giving a total of 1042 participants. Randomisation occurred between May 2010 and March 2012. The mean age of participants was 82.9 years, and 665 (64%) were female. No adverse events attributable to the intervention were recorded. Of the 1042 participants, 870 (83%) were included in the analysis of the primary outcome (intervention, n = 479; control, n = 391). The primary outcome showed no significant differences between groups. The adjusted mean difference in the BI score between groups was 0.19 points higher in the intervention arm [95% confidence interval (CI) –0.33 to 0.70, p = 0.48; adjusted intracluster correlation coefficient 0.09]. Secondary outcome measures showed no significant differences at all time points. Mean incremental cost of the Occupational Therapy intervention for residents with stroke living in UK Care Homes intervention was £438.78 (95% CI –£3360.89 to £1238.46) and the incremental QALY gain was 0.009 (95% CI –0.030 to 0.048). Limitations: A large proportion of participants with very severe activity-based limitations and cognitive impairment may have limited capacity to engage in therapy. Conclusion: A 3-month individualised course of OT showed no benefit in maintaining functional activity in an older care home population with stroke-related disabilities. Future work: There is an urgent need to reduce health-related complications caused by inactivity and to provide an enabling built environment within care homes. Trial registration: Current Controlled Trials ISRCTN00757750. Funding: This project was funded by the National Institute for Health Research Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 20, No. 15.